Chemical composition of ferromanganese nodules from the central Pacific Ocean as part of the "Hawaii-Tahiti Transect Program - W L Plüger; Günther Friedrich (PANGAEA, 2023)
Manganese nodules were retrieved during the SO06 (R/V Sonne) and COPANO (R/V Le Suroit) campaigns as part of the international "Hawaii-Tahiti Transect Program" initiated at the CCOP/SOPAC-IOC/IDOE International workshop on "Geology Mineral Resources and Geophysics of the South Pacific" in Suva, Fiji im September 1975. Their chemical composition was determined using X-ray fluorescence (XRF).